'That item is mine!' Consumer competitiveness and need for control: a study of internet auction bidding. (24th August 2010) - Nichols, Bridget Satinover; Flint, Daniel J.
This paper presents findings from an interpretive study concerning the social processes involved in the act of bidding on the internet auction site eBay.com. Interpretations of depth interviews provide insights to the dynamic social forum of internet auction sites and their dissimilarity from both traditional retail venues and online stores. Participants' stories suggest how competing and a desire to maintain community norms can create conflict in the form of a struggle for control. Following a grounded theory tradition, emergent themes are integrated with relevant research that involves behavioural, emotional and social structural components. This study contributes to our understanding of unique social psychological aspects of online consumer behaviour. We also discuss implications for marketers and researchers.